2020
DOI: 10.1038/s12276-020-0390-4
|View full text |Cite
|
Sign up to set email alerts
|

PROM2 promotes gemcitabine chemoresistance via activating the Akt signaling pathway in pancreatic cancer

Abstract: In recent years, the deoxycytidine analogue gemcitabine (2′,2′,-difluorodeoxycytidine) has become the first-line chemotherapeutic agent for patients with pancreatic cancer. However, due to the intrinsic resistance of pancreatic cancer cells, gemcitabine-based chemotherapy yields limited disease control, with >85% disease progression at 6 months from diagnosis. Therefore, elucidating the mechanisms of chemoresistance is a critical step in improving cancer therapy, especially for the treatment of pancreatic canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 55 publications
2
20
0
2
Order By: Relevance
“…It is important to mention that our data on sorafenib standard therapy on HCC (induction of late apoptosis and necroptosis) is fully in line with previous reports (Lin et al, 2017). The same was also true for gemcitabine which induced early and late apoptosis in our and other studies (Pauwels et al, 2009;Li et al, 2020). Similar to sorafenib, both LNP types induced late apoptosis, whereas sorafenib and E-LNPs also additionally induced necroptosis in the HCC cell line.…”
Section: E-lnps Induced Late Apoptosis and Necroptosis While Inhibiti...supporting
confidence: 91%
“…It is important to mention that our data on sorafenib standard therapy on HCC (induction of late apoptosis and necroptosis) is fully in line with previous reports (Lin et al, 2017). The same was also true for gemcitabine which induced early and late apoptosis in our and other studies (Pauwels et al, 2009;Li et al, 2020). Similar to sorafenib, both LNP types induced late apoptosis, whereas sorafenib and E-LNPs also additionally induced necroptosis in the HCC cell line.…”
Section: E-lnps Induced Late Apoptosis and Necroptosis While Inhibiti...supporting
confidence: 91%
“…Moreover, aspirin also shows a therapeutic potential through targeted inhibition on tumor growth and angiogenesis [19,20]. Many studies pointed out gemcitabine activation of Akt/mTOR signaling pathway in resistant cells is a key signaling event for gemcitabine resistance, and we suppose aspirin may resensitize resistant cells to gemcitabine by inhibiting this activated pathway [21][22][23]. Considering the above two points, when it comes to combining with aspirin, gemcitabine may be more suitable for research than 5FU, irinotecan, oxaliplatin, taxanes or other chemotherapeutic agents.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, cellular factors related to survival and apoptosis are linked to therapeutic resistance. A recent study showed that gemcitabine resistance is aggravated by an activation of AKT serine/threonine kinase (AKT) signaling; therefore, AKT inhibition augments the efficacy of gemcitabine by activating apoptotic cell death in vitro and in vivo [ 24 ]. In addition, extracellular signal-regulated kinase (ERK) positively regulates the level of anti-apoptosis factors such as B-cell CLL/lymphoma 2 ( BCL2 ), impeding caspase activations [ 25 ].…”
Section: Introductionmentioning
confidence: 99%